2019
DOI: 10.1111/ppa.12978
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of tomato leaf curl New Delhi virus in Italy: estimation of incidence and genetic diversity

Abstract: Tomato leaf curl New Delhi virus (ToLCNDV) is a bipartite begomovirus (family Geminiviridae) identified for the first time in 1995 in Asia, from where it spread into several countries of the Mediterranean basin. ToLCNDV was found in Spain in 2012, and subsequently in Tunisia and Italy. The first outbreak in Italy occurred at the end of 2015 in Trapani province (Sicily) on zucchini squashes. Then in 2016, ToLCNDV was found in infected zucchini plants in Campania, Lazio and Sardinia regions, and in 2017 in Calab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(55 citation statements)
references
References 31 publications
0
43
0
Order By: Relevance
“…In the last years, emerging viral diseases have been an important limiting factor for many crop production systems, such as tomato crops, causing considerable economic losses (Hanssen, Lapidot & Thomma, 2010). Greenhouse tomato production in Italy is affected by important losses that are caused by several different viruses: Pepino mosaic virus (Davino et al, 2017b, 2008; Tiberini et al, 2011), Tomato mosaic virus (ToMV), Tomato spotted wilt virus (Panno et al, 2012), Tomato leaf curl New Delhi virus (Panno et al, 2019), Tomato yellow leaf curl virus—Tomato yellow leaf curl Sardinia virus and their recombinants (Davino et al, 2009, 2012; Panno, Caruso & Davino, 2018) and Tomato brown rugose fruit virus (ToBRFV) detected at the end of 2018 (Panno, Caruso & Davino, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In the last years, emerging viral diseases have been an important limiting factor for many crop production systems, such as tomato crops, causing considerable economic losses (Hanssen, Lapidot & Thomma, 2010). Greenhouse tomato production in Italy is affected by important losses that are caused by several different viruses: Pepino mosaic virus (Davino et al, 2017b, 2008; Tiberini et al, 2011), Tomato mosaic virus (ToMV), Tomato spotted wilt virus (Panno et al, 2012), Tomato leaf curl New Delhi virus (Panno et al, 2019), Tomato yellow leaf curl virus—Tomato yellow leaf curl Sardinia virus and their recombinants (Davino et al, 2009, 2012; Panno, Caruso & Davino, 2018) and Tomato brown rugose fruit virus (ToBRFV) detected at the end of 2018 (Panno, Caruso & Davino, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…the pest has to be eradicated immediately if detected. However, the Panel notices the frequent report of outbreaks in Spain since 2013 (Table 3), and information from the literature suggesting that it might be more widespread in open field and in the environment than officially reported (Ju arez et al, 2019;Panno et al, 2019). 2017Source: EPPO GD, accessed on 24/2/2020.…”
Section: Pest Distribution In the Eumentioning
confidence: 99%
“…The genomes of ToLCNDV isolates are most diverse in Asia (Moriones et al, 2017) and as shown for many other geminiviruses, the genomes are shaped by recombination events comprising sequences of 1 The Pest Survey Card will be updated in the form of Story Map that will be available in the Plant Pests Story Maps Gallery available online: https://efsa.maps.arcgis.com/apps/MinimalGallery/index.html?appid=f91d6e95376f4a5da206eb1815ad1489 2 https://zenodo.org/record/2541541/preview/ribess-manual.pdf 3 https://shiny-efsa.openanalytics.eu/ other begomoviruses or sequences of unknown origin (Lefeuvre and Moriones, 2015). In contrast to the diversity of ToLCNDV genomes reported from India and Pakistan, the ToLCNDV isolates that are currently found in the EU are genetically uniform (99% nucleotide identity) and form a distinct cluster, well separated from isolates occurring outside the EU (Juárez et al, 2019;Panno et al, 2019). Because these isolates are <94% identical to world ToLCNDV isolates, these EU isolates comprise a specific strain, ToLCNDV-ES (Fortes et al, 2016;Ruiz et al, 2017).…”
Section: Introductionmentioning
confidence: 99%